Effects of sample location and sawing method on quality of oil palm wood - Hamzah, Nurul Nabilah (2016)
Decreasing of the rubberwood supply and increasing of world demand towards palm oil, significantly cause the abundant oil palm truck which is consider as an agriculture waste were investigate as a possible alternative as a future source of timber. In establishing oil palm wood as a potential wood substitute its own imperfection need to be enhance. To solve the problems, it is treated using chemical modification method known as Com-press. Continuation of the method done before, improvement was made and new method was invented known as Integrated Treatment Process. It consists of a six-step processing method (sawing, steaming and compression, drying, resin soaking, heating, and hot-pressing). In this study, effect of sample location and sawing method using Integrated Treatment Process was highlighted. The thickness of both slab shape was cut to 40 to 80 mm with 150 mm width and 300 mm in length. All slabs were treated with Low molecular weight phenol formaldehyde. This process used a reversed cant sawing method that not only produce normal square slab but also wane slab. Steaming was applied as pretreatment before the sample compressed to avoid excessive cracking. The formation of the micro-cracks facilitates resin inclusion. The sample then soaked instead of impregnation. The sample heated by semi-cured in an oven and finally compressed by using hot-press. The slab then tested to see it mechanical and physical properties. For mechanical properties static bending, compression parallel to grain, and shear tests were done and for physical properties water absorption and thickness swelling tests were applied. Result was analysis using computer statistical program, Statistical Package for the Social Sciences (SPSS) and complete randomized design analysis of variance (ANOVA). The results show that waney slab treated oil palm wood have better properties than square slab treated oil palm wood by almost 7 % for weight percentage gain, 113 kg/m³ higher for wood density, 0.9 % lower for water absorption percentage, and 0.3 % slightly lower for thickness swelling. Same goes for mechanical properties, waney slab treated oil palm wood have better mechanical properties compared to square slab treated oil palm wood. For bending strength, value of modulus of elasticity is 2325 N/mm² better than square slab treated oil palm wood, and value of modulus of rupture is 18 N/mm² higher. 1.9 N/mm² better value of shear strength of waney slab of treated oil palm wood calculated compared to square slab treated oil palm wood. Only compression strength parallel to grain for square slab found to be better than wane slab treated oil palm wood by 16 N/mm². As a whole, wane slab of treated oil palm wood have higher values of all tests but no specific slab thickness were obtained and gave the best result. Contradictory, value of compression parallel to grain gave result that is not complied as what was expected. In conclusion, the Integrated Treatment and Process do give effect on the quality of oil palm wood. It is proven fast, practical and economically viable for the industry.